Volume Stability of Cement Paste Containing Limestone Fines - Jamal Khatib; Rawan Ramadan; Hassan Ghanem; Adel Elkordi (Buildings, 2021)
The common cause of cracking in cement paste is shrinkage due to different reasons, such as loss of water and chemical reactions. Incorporating limestone fines (LF) as a cement replacement can affect the shrinkage of the paste. To examine this effect, five paste mixes were prepared with 0, 5, 10, 15 and 20% LF as a cement replacement and with a water-to-binder ratio (w/b) of 0.45. Four volume stability tests were conducted for each paste: chemical, autogenous and drying shrinkage and expansion. Chemical shrinkage was tested each hour for the first 24 h and thereafter every 2 days for a total period of 90 days. The drying shrinkage, autogenous shrinkage and expansion were monitored every 2 days until 90 days. The results showed that replacing 15% LF enhanced the chemical shrinkage of the paste. However, autogenous shrinkage of the paste was found to increase between 0 and 10% LF and decline sharply at 15 and 20% LF. Drying shrinkage was found to increase with the increase in LF content. Expansion exhibited little variation between 0 and 10% LF and an increase for replacement above 15% LF. These results are discussed in terms of the formation of hydration products and self-desiccation due to hydration.